(untitled) (Scientia Agropecuaria, 2021)
The consumer demand for chayote (Sechium edule (Jacq.) Sw.) fruits has increased in recent years, virens levis being the most important variety, although other chayote varieties are gaining importance such as nigrum xalapensis and n. spinosum. However, the postharvest behavior of these varieties is different, so it is important to evaluate the factors that limit the shelf life of each variety. Therefore, in this study, fruits of each variety from the Mexican National Germplasm Bank of Sechium edule were used. The following fruit quality variables were evaluated: weight loss, humidity (%), color, chlorophyll, titratable acidity, total soluble solids (TSS), total sugars, and stomatal characteristics. In addition, the storage potential of each variety was evaluated for two weeks at different temperatures, 7°, 13° (85% RH) and 24 °C (60% RH), with the application of 1-methylcyclopropene (1-MCP). The variables evaluated were viviparism, disease severity, weight loss, dehydration and chilling injury (CI). The fruits of n. xalapensis and n. spinosum have a higher content of chlorophylls and carotenoids, but similar contents of TSS, acidity and total sugars than v. levis fruits. The use of 1-MCP reduced viviparism in all varieties, and the severity of blisters was higher in v. levis. The fruits of the three varieties presented severe CI when stored at 7 °C but the most susceptible to dehydration and diseases severity is n. spinosum.